Analisa Pengaruh Variasi Tekanan Udara Pembakaran terhadap Efisiensi Pengujian pada Sistim Pembangkit Listrik Tenaga Uap Skala Laboratorium - Jatmiko Edi Siswanto (Universitas Batanghari Jambi, 2022)
This research is about comparing the efficiency of a laboratory-scale steam power plant with coconut shell charcoal as fuel. The test was carried out at the STITEKNAS Lab – JAMBI, with the data obtained in this test were steam power, shaft power and electrical power. The error in this study aims to determine the effect of pressure on the performance of a coconut shell charcoal power plant. steam used by wet steam researchers. The research methodology uses variations in combustion pressure (1,2 and 3 bar) to obtain research data.,From the test data of laboratory-scale research results with coconut shell charcoal as fuel, variations in combustion pressure in the furnace that the greater the combustion pressure will produce the higher combustion chamber temperature, the largest at a combustion pressure of 3 bar produces a combustion chamber temperature of 746 °C and the smallest at a pressure of 1 bar of 883.75 °C and from the calculation of research data obtained results of laboratory-scale steam turbine efficiency with coconut shell charcoal fuel the higher the combustion pressure the higher the power produced, the highest input power at a combustion pressure of 3 bar with a value of 27.26 watts and the smallest at a combustion pressure of 1 bar with a large input power of 22.94 bar, while in the calculation of efficiency, the efficiency of the combustion pressure is that the turbine efficiency is higher than the efficiency of the generator. 18% and at a combustion pressure of 3.Bar the lowest efficiency is obtained, namely the turbine efficiency of 51.36% while the generator efficiency is 17.5%, so that the increase in combustion pressure cannot increase the efficiency of the turbine and generator.